Dimension of Disaster and Coping Strategy in Nepal (1971–2020) - Regmi, Prakash; Regmi, Deepak (BMC Journal of Scientific Research, 2022)
The people of Nepal today, are victims to perform disaster events. The combined efforts of the government and non-government sectors are seemed to reduce the impacts of growing and changing disaster patterns. This article provides an overview and results of Nepal disaster vulnerability and achievements of the government and non-government efforts. The impact of efforts has been monitored on the based-on disaster and mortality rate of disaster. This study was carried out based on 42,878 total disaster events and 44,782 deaths that occurred within 50 years period (1971-2020). The information has been pulled from the website of the national planning commission for 15 different periodic plans. And for the disaster detail, statistical data (incidents and death) has been also carried out from the website. Some statistical tools were used for the analysis. Although the number of total deaths is increasing, the event/death ratio is decreasing. The pattern of disaster has been changing in Nepal. The planning and legal efforts seem somehow positive for the case death rate on average.